Direito à cultura: organizações da sociedade civil - Pato, Isabel Mattos Porto (2013)
The aim of this research is to examine the actions of civil society organizations in the cultural and artistic fields by identifying existing institutional profiles. Based on a historical context, in Brazil, three categories have been identified within the context of organized civil society working in the fields of art and culture organizations that provide cultural services, organizations that offer financial support to cultural projects and organizations that directly deal with populations and offer art and culture workshops. Working on the hypothesis of a fourth category, which would include organizations that develop actions related to the right to culture, this research examined the experience of Ação Educativa Assessoria, Pesquisa e Informação, which is an organization, stablished in 1994, whose work is guided by a human rights-based approach to art and culture. The organization focuses on artistic expressions produced in lowincome neighborhoods of the city of São Paulo, which are part of a more comprehensive movement known as cultura de periferia. This study is based on Marilena Chaui s concept of cultural citizenship, on the understanding of culture as a tool for social change and on the full right to culture: access, fruition, production and creation. Raymond Williams s concept of culture, its dimensions of popular culture and culture is ordinary. This is a challenging moment for civil society organizations with respect to their political and financial sustainability, since their reliability is being questioned and they have been facing project-funding difficulties. In view of this situation, they must reinvent themselves. And, certainly, getting connected with the cultural and artistic fields is a way of both reinventing themselves and expanding their scope of action. The increase in the number of cultural public programs has enabled this connection and has become an opportunity. These organizations have emerged from popular education and from the support to social movements; therefore, their actions are rooted in this way of thinking. In addition, when organizations deal with the human right to culture, they become spaces that foster the fight against social inequalities, as well as social transformation and a new project of society. The methodology of this research is a multidisciplinary analysis of the facts in its political, anthropologic/culture dimensions. Based on the bibliographic references and on the field research as strategies of analysis, as realization of interviews and participation on some events organized by Ação Educativa